Construction of a tiered training model for laparoscopic techniques in urology - DONG Dexin, ZHANG Yushi (Jichu yixue yu linchuang, 2024)
With the development of laparoscopic technology in urology, the training of laparoscopic technology operator plays an extremely important role in the specialized education process from medical students to specialist physicians. With various medical students being included in standardized training for specialized physicians, many problems such as uneven quality of trainees appeared, lack of standardization in the training process, deviation in training target positioning, and insufficient quality control management methods. This article explored the construction of a standardized tiered training system for laparoscopic techniques in the urology department of Peking Union Medical College Hospital, including cultural construction, training mode system, assessment mechanism and trainers′ development. By constructing the special model for laparoscopic technology training in urology, it would lay a solid foundation and provide experience for building a standardized training system of laparoscopy in urology.